Residual stress induced stabilization of martensite phase and its effect on the magnetostructural transition in Mn-rich Ni-Mn-In/Ga magnetic shape-memory alloys - Singh, Sanjay; Kushwaha, Pallavi; Scheibel, Franziska; Liermann, Hanns-Peter; Barman, S. R.; Acet, M.; Felser, Claudia; Pandey, Dhananjai (Physical Review B - Condensed Matter and Materials Physics, 2015)
The irreversibility of the martensite transition in magnetic shape memory alloys (MSMAs) with respect to the external magnetic field is one of the biggest challenges that limits their application as giant caloric materials. This transition is a magnetostructural transition that is accompanied with a steep drop in magnetization (i.e.,ΔM) around the martensite start temperature (Ms) due to the lower magnetization of the martensite phase. In this Rapid Communication, we show that ΔM around Ms in Mn-rich Ni-Mn-based MSMAs gets suppressed by two orders of magnitude in crushed powders due to the stabilization of the martensite phase at temperatures well above Ms and the austenite finish (Af) temperatures due to residual stresses. Analysis of the intensities and the FWHM of the x-ray powder-diffraction patterns reveals stabilized martensite phase fractions as 97%, 75%, and 90% with corresponding residual microstrains as 5.4%, 5.6%, and 3% in crushed powders of the three different Mn-rich Ni-Mn alloys, namely, Mn1.8Ni1.8In0.4, Mn1.75Ni1.25Ga, and Mn1.9Ni1.1Ga, respectively. Even after annealing at 773 K, the residual stress stabilized martensite phase does not fully revert to the equilibrium cubic austenite phase as the magnetostructural transition is only partially restored with a reduced value of ΔM. Our results have a very significant bearing on the application of such alloys as inverse magnetocaloric and barocaloric materials.
CRIS-Team Scopus Importer:2023-03-20